2018
DOI: 10.15226/2577-7815/2/2/00122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treasury Single Account (Tsa) on Deposit Money Banks’ Liquidity Performance in Nigeria

Abstract: This paper investigated effect of Federal Government of Nigeria (FGN) Deposit Withdrawals into the Treasury Single Account (TSA) on Deposit Money Banks’ liquidity performance in Nigeria. Secondary data were obtained from [7] Central Bank of Nigeria (CBN) Statistical Bulletin covering pre and post implementation years (2012 to 2017). The dependent variable was represented by Deposit Money banks’ liquidity ratiowhile the independent variable was represented by Federal Government Deposits at the Deposit Money Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The regression results further revealed that, while foreign and state-owned banks were more resilient, private, and domestic banks' performance deteriorated after TSA adoption. The findings are consistent with the finding by (Ajetunmobi,et al,017), (Muraina, 2018), (Mwambuli & Igoti, 2021), and (Ndubuaku, et al, 2017) whose finding revealed that the TSA had a negative impact on performance of banks. (Mawalla, 2023) examined the Implications of the Treasury Single Account (TSA) on Tanzanian Banks focusing on profitability, efficiency, and stability, using Return on Assets (ROA), Return on Equity (ROE) and Non-Performing Loans (NPL) as performance parameters.…”
Section: Empirical Literature Reviewsupporting
confidence: 93%
See 2 more Smart Citations
“…The regression results further revealed that, while foreign and state-owned banks were more resilient, private, and domestic banks' performance deteriorated after TSA adoption. The findings are consistent with the finding by (Ajetunmobi,et al,017), (Muraina, 2018), (Mwambuli & Igoti, 2021), and (Ndubuaku, et al, 2017) whose finding revealed that the TSA had a negative impact on performance of banks. (Mawalla, 2023) examined the Implications of the Treasury Single Account (TSA) on Tanzanian Banks focusing on profitability, efficiency, and stability, using Return on Assets (ROA), Return on Equity (ROE) and Non-Performing Loans (NPL) as performance parameters.…”
Section: Empirical Literature Reviewsupporting
confidence: 93%
“…Ultimately, this withdrawal of Government Deposits impacts negatively on their lending ability since banks need deposits (liabilities) to provide Loans and Advances. The findings are in agreement with the findings of the studies done by (Kanu, 2016), (Muraina, 2018), (Mwambuli & Igoti, 2021), (Ajetunmobi, et al, 2017), (Ndubuaku, et al, 2017), and (Mkaro, et al, 2023) whose findings revealed that the TSA impacts negatively on the performance of the banking sector. These findings point to Commercial Banks' reliance on Government Deposits, to Mobilize Deposits and thus provide lending.…”
Section: Conclusion and Recommendations 61 Conclusionsupporting
confidence: 92%
See 1 more Smart Citation